The Model of a School and Family Communication - Juškienė, Vaiva; Stasiulienė, Vilija (Pedagogika, 2019)
This article deals with the problem of cooperation between the family and a school. The lack of positive communication between family and school becomes the main bother for students to understand better themselves, to learn more about the needs for self-expression and possibilities for further professional development.From one side, parents are not always satisfied with emotional and intellectual support coming from school. From another side, teachers reflect on the lack of family motivation in cooperating with the school in order to help students to develop their own life perspectives.The aim of the research is to validate theoretically and empirically the model of communication between family and a school. The objectives: 1) Highlighting the theoretical perspective of the conception, methods, and ways of the cooperation with family and a school. 2) To disclose the activities of N school and their sociocultural context. 3) To develop the theoretical model of communication between family and a school and to validate it empirically. The authors have created the model of communication for non-formal and education for carrier activities through theoretical sources and practical educational activities. The model is tested empirically. It is assumed, that the created model effectively improves collaboration between the family and the school and consists of 4 components: the aims for educational communication; structural parts, reflecting communication activities in non-formal and educational carrier activities; available and predictive shortcomings in communication; ways of implementing and improving effective communication between family and the school.